An assessment of primary health care costs and resource requirements in Kaduna and Kano, Nigeria - Ogundeji, Yewande; Abubakar, Hamza; Ezeh, Uche; Hussaini, Tijjani; Kamau, Nelson; Love, Eliza; Muñoz, Rodrigo; Ongboche, Paul; Opuni, Marjorie; Walker, Damian G.; Gilmartin, Colin (Frontiers in Public Health, 2023)
Introduction The availability of quality primary health care (PHC) services in Nigeria is limited. The PHC system faces significant challenges and the improvement and expansion of PHC services is constrained by low government spending on health, especially on PHC. Out-of-pocket (OOP) expenditures dominate health spending in Nigeria and the reliance on OOP payments leads to financial burdens on the poorest and most vulnerable populations. To address these challenges, the Nigerian government has implemented several legislative and policy reforms, including the National Health Insurance Authority (NHIA) Act enacted in 2022 to make health insurance mandatory for all Nigerian citizens and residents. Our study aimed to determine the costs of providing PHC services at public health facilities in Kaduna and Kano, Nigeria. We compared the actual PHC service delivery costs to the normative costs of delivering the Minimum Service Package (MSP) in the two states. Methods We collected primary data from 50 health facilities (25 per state), including PHC facilities—health posts, health clinics, health centers—and general hospitals. Data on facility-level recurrent costs were collected retrospectively for 2019 to estimate economic costs from the provider’s perspective. Statewide actual costs were estimated by extrapolating the PHC cost estimates at sampled health facilities, while normative costs were derived using standard treatment protocols (STPs) and the populations requiring PHC services in each state. Results We found that average actual PHC costs per capita at PHC facilities—where most PHC services should be provided according to government guidelines—ranged from US 18.9 to US 28 in Kaduna and US 15.9 to US 20.4 in Kano, depending on the estimation methods used. When also considering the costs of PHC services provided at general hospitals—where approximately a third of PHC services are delivered in both states—the actual per capita costs of PHC services ranged from US 20 to US 30.6 in Kaduna and US 17.8 to US 22 in Kano. All estimates of actual PHC costs per capita were markedly lower than the normative per capita costs of delivering quality PHC services to all those who need them, projected at US 44.9 in Kaduna and US 49.5 in Kano. Discussion Bridging this resource gap would require significant increases in expenditures on PHC in both states. These results can provide useful information for ongoing discussions on the implementation of the NHIA Act including the refinement of provider payment strategies to ensure that PHC providers are remunerated fairly and that they are incentivized to provide quality PHC services.